(untitled) (Research, Society and Development, 2023)
The present research focuses on the use of experimental activities carried out with alternative materials in Chemistry classes at a public school in the municipality of Dom Pedrito. The main focus is to investigate whether the use of these activities can or cannot enhance the teaching and learning process in Chemistry. Thus, we aimed to answer the following question: How to enhance the teaching and learning process in Chemistry through the use of experimental activities with alternative and low-cost materials in public schools in the city of Dom Pedrito? The target audience consisted of 9th-grade students from a public school in the municipality. Two didactic sequences (DS) based on experimental activities and alternative materials were developed and implemented. The results revealed significant contributions regarding students’ learning.